A disconnectivity index for improving choices in managing protected areas for rivers. (June 2016) - Rivers‐Moore, Nick; Mantel, Sukhmani; Ramulifo, Pfananani; Dallas, Helen
Abstract: Ecological processes in freshwater lotic systems are disrupted when upstream–downstream connectivity is broken. Changes in catchment land use, catchment density of small dams, and instream impoundments result in changes to thermal and flow regimes, which in turn affect natural biological turnover patterns and rates, as well as organism exchange and dispersal. This study describes the development of a comprehensive connectivity index for rivers, and how this can be used as a spatial product to prioritize areas of freshwater importance within the province of KwaZulu‐Natal, South Africa. A longitudinal connectivity index (i.e. in‐channel barriers) reflected as a cumulative downstream score, as well as the characterization of these barriers as a spectrum from absolute to partial, was developed for the main rivers in the province of KwaZulu‐Natal, South Africa. This was combined with a lateral connectivity index based on the effects of catchment fragmentation and a density index for small dams. The impacts of instream barriers on flow and water temperature time series were assessed using metrics describing magnitude, frequency, duration and timing of thermal and flow events for time series before and after impoundment. These impacts were spatially mapped using a surrogate function that related reset distance to average discharge, and the assumption that should the unimpounded downstream river length exceed the reset distance, the river species patterns would revert to natural conditions. It is concluded that a multi‐metric connectivity surface should be used as a cost layer for freshwater conservation plans for the province. Assessed in tandem with protected areas, it provides a tool for setting priorities for whole river systems suitable for immediate conservation versus systems that may require rehabilitation. Copyright © 2016 John Wiley & Sons, Ltd.